Peran Kelompok Tani dalam Program Kemitraan Konservasi secara Syariah pada Balai Besar Taman Nasional Gunung Leuser - Andi Fauzan R. Pohan; Muhammad Zainal Abidin (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This research aims to determine the role of the Conservation Forest Farmer Group (KTHK) in the conservation partnership program and the income level of the Conservation Forest Farmer Group (KTHK) in Gumpang Lempuh Village, Putri Betung District, Gayo Lues Regency. The results of the research show that there is a very significant role of farming communities who are members of the Conservation Forest Farmers Group (KTHK), there is a high active role of participation from farming communities who are members of KTHK in the implementation stages of the conservation partnership program in Gumpang Lempuh village, Putri Betung District, Gayo Regency Lues. The results of this research show a very significant role from members of the Conservation Forest Farmers Group (KTHK) in Gumpang Lempuh Village, Putri Betung District, Gayo Lues Regency in the program. This is evident from the data obtained in the field at each stage of the conservation partnership program in Gumpang Lempuh Village, Putri Betung District, Gayo Lues Regency, which is very high. The five types of forestry commodities that have been produced by the Geumpang Lempuh Village Conservation Forest Farmers Group in this partnership program include chilies, cocoa, candlenuts, bananas and ginger.